The safety and efficacy of AphtoFix® mouth ulcer cream in the management of recurrent aphthous stomatitis. Issue 1 (December 2016) - Sakly, Amina; De Wever, Bart; Jutla, Balraj; Satia, Milan; Bogaert, Jean
Abstract Background Recurrent Aphthous stomatitis (RAS) is a prevalent ulcerative and painful disorder of the oral cavity with unknown etiology and for which no efficient treatment is currently available. The present study aimed to evaluate the safety and the efficacy of AphtoFix®, a new mouth ulcer cream that was developed to help treat RAS. Prior to launching the product on the market, two initial safety assessment studies were performed. Subjects and methods In a first study, the in vitro biocompatibility of AphtoFix® was evaluated on reconstructed human gingival tissue models according to ISO guidelines 10993. In a second study, the tolerability of AphtoFix® was evaluated in 20 subjects during a 4-weeks daily application in the mouth. The third study investigated both the safety and efficacy of AphtoFix® treatment on 19 patients suffering from RAS. This study was done in compliance with the Helsinki Declaration. Results The results of in vitro biocompatibility study showed that AphtoFix® mouth ulcer cream did not induce any detectable cytotoxicity and irritation. These observations were confirmed in the 4 weeks tolerability study where no undesired of adverse reactions were noticed. The results of the post-market clinical efficacy study demonstrated a clear reduction in ulcer size from baseline after 3 days treatment (p  < 0.05). Pain intensity reduction was also observed in all subjects. Conclusion The application of AphtoFix® did not induce any undesired skin or mucosa reactions. These initial findings demonstrate that AphtoFix® is safe and efficient in reducing ulcer size and decreasing the pain intensity induced by ulcers. Trial registration Clinical trial Registry India Nr.CTRI201408004918, Date of registration: 22/08/2014